The Influence of Education Level and Work Environment on Employee Performance Mallawa Subdistrict Office Maros. - Wahyu Erdiansyah; Muchriady Muchran; Andi Risfan Rizaldi (International Journal of Economic Research and Financial Accounting, 2024)
The purpose of this study is a type of quantitative research with the aim of determining the effect of education level and work environment on the performance of Mallawa District office employees, Maros Regency. This sample was taken from the Mallawa sub-district office of Maros Regency. The type of data used in this study is quantitative data obtained from questionnaires that are shared and relate to the problem under study. Data collection is carried out by observation and distribution of questionnaires. In this study, the data sources used in data collection include primary data and secondary data. The research instrument used in this study used the Likert scale method. Based on the results of data research using statistical calculations through the Statistical Package for the Social Science (SPSS) version 29 application regarding the influence of education level and work environment on the performance of Mallawa Subdistrict office employees of Maros Regency which has been discussed from the previous chapter, the author draws an important conclusion, namely the level of education and work environment have a positive and significant effect on employee performance..